2014
DOI: 10.1182/blood-2014-01-549360
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag and high-dose dexamethasone as frontline treatment of newly diagnosed immune thrombocytopenia in adults

Abstract: Key Points• Eltrombopag/dexamethasone is a safe and effective combination for treating newly diagnosed ITP patients.• This treatment may prove useful in achieving lasting responses without additional immunosuppression in some patients.Immune thrombocytopenia (ITP) results from platelet destruction and production suppression. Eltrombopag belongs to a new class of thrombopoietin-mimetic drugs that raise platelet counts in ITP patients. We performed a single-arm study to assess the response to a single course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 20 publications
6
59
1
Order By: Relevance
“…All patients quickly responded and most reached CR, similarly to previous experience with eltrombopag and rituximab plus HDD (Gómez‐Almaguer et al , , ). The present report can attest to the efficacy of more aggressive therapy early in the course of ITP as it led to an RFS of almost 80% at 12 months that was sustained, in contrast to 66·7% in our previous report with eltrombopag plus HDD (Gómez‐Almaguer et al , ). Our previous experience with rituximab and HDD showed a similar RFS (84%) at 12 months (Gómez‐Almaguer et al , ).…”
Section: Characteristics and Outcomes Of 13 Adults With Newly Diagnossupporting
confidence: 82%
“…All patients quickly responded and most reached CR, similarly to previous experience with eltrombopag and rituximab plus HDD (Gómez‐Almaguer et al , , ). The present report can attest to the efficacy of more aggressive therapy early in the course of ITP as it led to an RFS of almost 80% at 12 months that was sustained, in contrast to 66·7% in our previous report with eltrombopag plus HDD (Gómez‐Almaguer et al , ). Our previous experience with rituximab and HDD showed a similar RFS (84%) at 12 months (Gómez‐Almaguer et al , ).…”
Section: Characteristics and Outcomes Of 13 Adults With Newly Diagnossupporting
confidence: 82%
“…A small study of newly diagnosed adult patients with ITP who received first-line treatment with 4 days of dexamethasone in combination with eltrombopag showed that 100% of them achieved platelet counts of $30 3 10 9 /L at 1 month. 47 Sustained responses with platelets $100 3 10 9 /L at 6 months were achieved in 50% of patients. 47 At 1 year, 66.7% had relapse-free survival.…”
Section: Other Indications and Future Directionsmentioning
confidence: 96%
“…47 Sustained responses with platelets $100 3 10 9 /L at 6 months were achieved in 50% of patients. 47 At 1 year, 66.7% had relapse-free survival. 47 Results from multicenter trials studying the outcomes of early eltrombopag therapy for children with ITP are forthcoming.…”
Section: Other Indications and Future Directionsmentioning
confidence: 96%
See 1 more Smart Citation
“…There were 12 adults in this study, and 9/12 patients (75%) had a platelet count $30 3 10 9 /L at 6 months and 8/12 (67%) at 12 months. 63 These preliminary data are interesting, but additional studies with more patients are needed to evaluate the long-term outcomes and better characterize toxicities with these alternative regimens.…”
mentioning
confidence: 99%